Advertisement Remove all ads

Factorize Each of the Following Algebraic Expression: A2 + 4b2 − 4ab − 4c2 - Mathematics

Sum

Factorize each of the following algebraic expression:
a2 + 4b2 − 4ab − 4c2

Advertisement Remove all ads

Solution

\[49 - x^2 - y^2 + 2xy\]
\[ = 49 - ( x^2 - 2xy + y^2 )\]
\[ = 49 - ( x^2 - 2 \times x \times y + y^2 )\]
\[ = 7^2 - (x - y )^2 \]
\[ = [7 - (x - y)][7 + (x - y)]\]
\[ = (7 - x + y)(7 + x - y)\]
\[ = (x - y + 7)(y - x + 7)\]

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RD Sharma Class 8 Maths
Chapter 7 Factorization
Exercise 7.6 | Q 26 | Page 23
Advertisement Remove all ads

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×